Thailand's industrialization and its consequences - Krongkaew, Medhi, ed
An outgrowth of the conference, "The Making of a Fifth Tiger? Thailand's Industrialization and its Consequences," held at the Australian National University on 7-9 December 1992."
Keywords: Industrialization -- Thailand -- Congresses; Thailand -- Economic conditions -- Congresses; Thailand -- Social conditions -- Congresses